Environmental conditions and physiological state influence estuarine movements of homing sockeye salmon. (1st July 2015) - Drenner, S. Matthew; Hinch, Scott G.; Martins, Eduardo G.; Furey, Nathan B.; Clark, Timothy D.; Cooke, Steven J.; Patterson, David A.; Robichaud, David; Welch, David W.; Farrell, Anthony P.; Thomson, Richard E.
Abstract The reproductive migration of anadromous salmonids through estuarine waters is one of the most challenging stages of their life cycle, yet little is known about the environmental and physiological conditions that influence migratory behaviour. We captured, sampled tissues, tagged and released 365 sockeye salmon (Oncorhynchus nerka) homing through inner coastal waters towards the Fraser River, British Columbia, Canada. Biotelemetry was used to assess the behaviour of individual sockeye salmon approaching estuarine waters and at river entry, which were related to both fish physiological condition at release and to prevailing environmental conditions. Sockeye salmon tended to stay close to the shore, migrated during the day, and movements were related to tide. Sockeye salmon migration rate was linked to wind‐induced currents, salinity and an individual's physiological state, but these factors were specific to location and stock. We propose that wind‐induced currents exposed sockeye salmon entering the estuary to stronger olfactory cues associated with Fraser River water, which in turn resulted in faster migration rates presumably due to either an increased ability for olfactory navigation and/or advanced reproductive schedule through a neuroendocrine response to olfactory cues. However, once the migration had progressed further into more concentrated freshwater of the river plume, sockeye salmon presumably used wind‐induced currents to aid in movements towards the river, which may be associated with energy conservation. Results from this study improve our biological understanding of the movements of Fraser River sockeye salmon and are also broadly relevant to other anadromous salmonids homing in marine environments.